THE IMPACT OF USING INSTRUCTIONAL UNITS ACCORDING TO THE PRESSLEY MODEL ON THE TEACHING JAVELIN HURLING TO STUDENTS - Assis. Prof. Dr. Ali Khawam Khateeb (American Journals, 2023)
The current research aims to investigate the impact of using instructional units based on the Pressley model in teaching of javelin Hurling to students. The researcher employed an experimental approach to fulfill the research requirements. The research procedures involved selecting a sample of third-year students majoring in Physical Education and Sports Sciences at the College of Basic Education, Mustansiriya University. The sample consisted of fifty-two students, equally divided into experimental and control groups.Pre-tests were conducted, and the instructional units were implemented using the Pressley model. After completing the educational program, which lasted for eight instructional units, the researcher administered a post-test to measure the javelin Hurling skills. The results indicated a positive impact on the learning of javelin Hurling skills among the experimental group students.The results were interpreted, and recommendations were provided by the researcher, emphasizing the importance of adopting instructional units prepared according to the Pressley model in teaching various other skills and activities.
Keywords: Hurling, javelin, skill, Pressley, Model.